2022
DOI: 10.3390/cancers14235776
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of RNA Polymerase I Stability and Function

Abstract: RNA polymerase I is a highly processive enzyme with fast initiation and elongation rates. The structure of Pol I, with its in-built RNA cleavage ability and incorporation of subunits homologous to transcription factors, enables it to quickly and efficiently synthesize the enormous amount of rRNA required for ribosome biogenesis. Each step of Pol I transcription is carefully controlled. However, cancers have highjacked these control points to switch the enzyme, and its transcription, on permanently. While this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 219 publications
1
14
0
Order By: Relevance
“…As in Fig 2D and 2E , the signal for RPA194 decreased in the RPA12 knockdown cells ( Fig 3B ). As previously documented [ 3 , 12 ], BMH-21 treatment led to a robust decrease in RPA194 nucleolar staining in both the control and RPA12 depleted cells ( Fig 3A and 3B ).…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…As in Fig 2D and 2E , the signal for RPA194 decreased in the RPA12 knockdown cells ( Fig 3B ). As previously documented [ 3 , 12 ], BMH-21 treatment led to a robust decrease in RPA194 nucleolar staining in both the control and RPA12 depleted cells ( Fig 3A and 3B ).…”
Section: Resultssupporting
confidence: 87%
“…RNA Polymerase I (Pol I) is a multi-subunit enzyme that operates in the nucleolus of the cell [ 1 3 ]. The key enzymatic activity of Pol I is to transcribe the ribosomal DNA (rDNA) into the 13 kb long 47S precursor ribosomal RNA (rRNA), which is the first step of the complex, resource and energy-consuming process of ribosome biogenesis [ 1 , 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter property is shared with Aminacrine, Ethacridine and two aminoquinolines; Amodiaquine and Amopyroquine ( 11 ). The capacity to induce degradation of POLR1A has been proposed as a relevant cytotoxic mechanism of BMH-21 ( 18 ). Our previous studies using BMH-21 confirmed that it is a potent inhibitor of Pol I, ribosome biogenesis and induces cell death.…”
Section: Introductionmentioning
confidence: 99%